Skill- biased effect of the technological change and income inequality: a cross country analysis - Calzoni, Giuseppe; Perugini, Cristiano; Pompei, Fabrizio (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2007)
The introduction of new technologies and organisational changes produces direct effects not only on the demand for skilled workers, at the expense of unskilled ones, but also on the upward wage dynamics of the former and on the wage decline of the latter. Depending on various social, economic and structural factors, the exacerbation of wage disparities may in turn produce effects on income re-distribution, as evidenced by extensive literature. In this paper, we propose a theoretical and empirical analysis in two connected steps. The first aims at investigating theoretically and empirically the changes in labour demand produced, among other factors, by the introduction of new technologies. In the second step, information about qualitative evolution of labour demand is examined, among other traditional determinants, as a factor affecting income distribution. The empirical analysis is carried out for a set of eastern and western EU countries
Argumenta Oeconomica, 2007, No 1-2 (19), s. 63-98
Keywords: technological change; skill-biases effect; income distribution